STUDY THE ANTIBACTERIAL ACTIVITY OF AQUEOUS EXTRACTION OF ONION (Allium cepaL) AGAINST Staphylococcus aureus ISOLATED FROM OTITIS MEDIA. - &et al., Ibrahim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to determine the antibacterial activity of onion (Allium cepaL.) aqueous extract against S. aureus bacteria isolated from patients with otitis media. Twenty swabs samples were taken from patients with otitis infection; these samples were cultured on different agar media .Results revealed that half of these isolates were related to S. aureus and the five of these isolates were subject to sensitivity test against several antibiotic groups. Most of isolates 100% were resistance to amoxicillin, chloramphenicol, cefoxitin and pencillin, and 60 % of were showed resistance to cefotaxtime and tetracycline, where as 20 % were resistance to Ciprofloxacin. Depending on the results of antibiotic sensitivity, the two isolates(S2,S5) were chosen for determining the minimum inhibitory concentration (MIC) test, S2 isolate showed high-level of resistance at (16 and 128 µg/ml) to chloraemphenicol, amoxicillin, ampicillin and Cefotaxime respectively, while S5 at concentration (32, 64 and 128 µg) were resistance to amoxicillin, ampicillin, chloraemphenicol and cefotaxtime. The MIC of onion extract against S. aureus was determined at two incubation periods The results were indicated that after 24 hrs, MIC of extract at 64 µg/ml was affected in inhibit the growth of S2 isolate, While 32 µg/ml was inhibited the growth of S5 isolate.However, after 72 hrs, It was found that the MIC at 32, 64 and 128 µg/ml were more effective in inhibited the growth of S2 and S5 isolates.